2015
DOI: 10.1038/mp.2015.100
|View full text |Cite
|
Sign up to set email alerts
|

De novo deleterious genetic variations target a biological network centered on Aβ peptide in early-onset Alzheimer disease

Abstract: We hypothesized that de novo variants (DNV) might participate in the genetic determinism of sporadic early-onset Alzheimer disease (EOAD, onset before 65 years). We investigated 14 sporadic EOAD trios first by array-comparative genomic hybridization. Two patients carried a de novo copy number variation (CNV). We then performed whole-exome sequencing in the 12 remaining trios and identified 12 non-synonymous DNVs in six patients. The two de novo CNVs (an amyloid precursor protein (APP) duplication and a BACE2 i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
88
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 97 publications
(92 citation statements)
references
References 57 publications
4
88
0
Order By: Relevance
“…ID fam, family code; MC, number of mutations carriers in the family; AOO, age of onset ranges in the family; DD, disease duration (at death or last examination); APOE, Apolipoprotein E genotype; F, familial; S, sporadic; Y, yes, U, unknown.* Indicates a previously reported de novo mutation in a sporadic case [20, 21, 40]. …”
Section: Resultsmentioning
confidence: 99%
“…ID fam, family code; MC, number of mutations carriers in the family; AOO, age of onset ranges in the family; DD, disease duration (at death or last examination); APOE, Apolipoprotein E genotype; F, familial; S, sporadic; Y, yes, U, unknown.* Indicates a previously reported de novo mutation in a sporadic case [20, 21, 40]. …”
Section: Resultsmentioning
confidence: 99%
“…The MARK4 variant was located in the linker domain and the VPS35 variant just 5 codons away from a mutation causing Parkinson disease and with demonstrated distinct functional effects [113,114] . The apparent specificity of these short regions and the weak probability that a variant would hit these regions in multiple individuals by chance may explain why there is currently no evidence of an association at the variant or gene levels.…”
Section: How To Deal With the Extreme Rarity Of Genetic Variants? Thementioning
confidence: 99%
“…Second, we performed WES in the 12 remaining trios and identified 12 nonsynonymous DNVs in 6 patients. The two de novo CNVs and 3 out of 12 nonsynonymous DNVs (in PSEN1 , VPS35 , and MARK4 ) targeted genes involved in a biological network centered on the Aβ peptide [113] . After computing the relative size of jointly covered bases of this a priori defined genetic network (323 genes) as well as estimating its relative mutability through the burden of inherited variants, we showed that this network was significantly enriched in amino acid-altering DNVs, compared to the rest of the exome.…”
Section: How To Deal With the Extreme Rarity Of Genetic Variants? Thementioning
confidence: 99%
See 1 more Smart Citation
“…Mutations in the PSEN1 gene account for the majority of AD-EOAD cases with 221 pathogenic mutations reported to date (http://www.alzforum.org/), including 6 deletions of PSEN1 exon 9 resulting either from splicing mutations (Perez-Tur et al, 1995;Sato et al, 1998;Rovelet-Lecrux et al, 2015) or genomic deletions (Prihar et al, 1999;Hiltunen et al, 2000;Smith et al, 2001).…”
Section: Introductionmentioning
confidence: 99%